Analysis by Finite Element Calculations of Light Scattering in Laser-textured AZO Films for PV thin-film Solar Cells. (December 2015) - Canteli, D.; López, J.M.; Lauzurica, S.; Lluscà, M.; Sánchez-Aniorte, M.I.; Bertomeu, J.; Morales, M.; Molpeceres, C.
Abstract: In the thin-film photovoltaic industry, to achieve a high light scattering in one or more of the cell interfaces is one of the strategies that allow an enhancement of light absorption inside the cell and, therefore, a better device behavior and efficiency. Although chemical etching is the standard method to texture surfaces for that scattering improvement, laser light has shown as a new way for texturizing different materials, maintaining a good control of the final topography with a unique, clean, and quite precise process. In this work AZO films with different texture parameters are fabricated. The typical parameters used to characterize them, as the root mean square roughness or the haze factor, are discussed and, for deeper understanding of the scattering mechanisms, the light behavior in the films is simulated using a finite element method code. This method gives information about the light intensity in each point of the system, allowing the precise characterization of the scattering behavior near the film surface, and it can be used as well to calculate a simulated haze factor that can be compared with experimental measurements. A discussion of the validation of the numerical code, based in a comprehensive comparison with experimental data is included.